Trusting the process. Implementing process goals for inexperienced and struggling athletes - Bright, L. (Techniques Magazine, 2012)
Unfortunately, coaches in every sport often put too strong an emphasis on outcome goals. Although these types of goals can provide motivation to get better, for many inexperienced athletes they are only good for pointing out shortcomings. In order to keep athletes motivated and excited to compete, process goals are essential. It would be beneficial for every difficult practice and competition to have at least one process goal that the coach and athlete can discuss, regardless of the performance for that day. Process goals can aid coaches in teaching positive habits, thoughts and behaviors. Author presents some suggested process goal behaviors and cues that can be used for runners.